Factors determine the decision to become a customer in a sharia bank - Abdillah Ubaidi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2017)
This study aims to determine the influence of the factors that determine the decision to become a customer in a sharia bank. Respondents in this study are customers who use Islamic banking products amounting to 50 people in the branch office of Bank Syariah Mandiri Kepanjen. Data collection techniques using questionnaires and analysis techniques using multiple regression. The results show that location, service, religiosity, Islamic economy and social behavior have a positive influence on the decision to become customers of sharia banks, while knowledge factors do not lead to the decision to become customers in Islamic banks.